2012
DOI: 10.1007/s00381-011-1674-8
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary endoscopic assisted surgery of a patient with a complete transorbital intracranial impalement through the dominant hemisphere

Abstract: (2012). Interdisciplinary endoscopic assisted surgery of a patient with a complete transorbital intracranial impalement through the dominant hemisphere. Child's Nervous System, 28(6) The ipsilateral eye, which had been shifted laterally, showed no deficits. In this case the combined transnasal-transcranial approach allowed safe and successful removal of the foreign object and the boy returned to everyday life with a favourable neurological outcome after one year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Vascular injury was noted in two patients (6%): one patient with right internal carotid artery and right posterior cerebral artery occlusion, and one patient with carotid-cavernous fistula. 1,4 A summary of findings from the systematic review is shown in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vascular injury was noted in two patients (6%): one patient with right internal carotid artery and right posterior cerebral artery occlusion, and one patient with carotid-cavernous fistula. 1,4 A summary of findings from the systematic review is shown in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, most cases (6/8 [75%]) of permanent blindness in our review were attributed to optic nerve injury. 1,2,4,11,[19][20][21][22] Also, vascular injury with a purely transorbital trajectory can be common because the FB traveling at a low velocity is often directed by the cone-shaped orbit to the cavernous sinus and carotid. 1,2 FBs with a transorbital only trajectory often present with an orbital or intracranial hematoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation